The Impact Of Financial Literacy On Human Capital Development In Micro, Small And Medium Enterprises - Erwin Ernestus Kadar Slamet (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This qualitative study aims to explore the impact of financial literacy on human capital development within micro, small, and medium enterprises (MSMEs). The research utilizes a descriptive qualitative approach to delve into the intricate relationship between financial literacy and human capital enhancement. Sampling technique employed purposive sampling to select MSMEs owners and employees who possess varying degrees of financial literacy. Data analysis involves thematic analysis, allowing for the identification of recurring patterns and themes within the collected data. The findings underscore the pivotal role of financial literacy in fostering human capital development within MSMEs, highlighting its significance in promoting entrepreneurial success, enhancing decision-making processes, and facilitating business growth. This study contributes to the existing body of knowledge by providing insights into the mechanisms through which financial literacy influences human capital development within the context of MSMEs.